Analyzing the relationship between self-efficacy and impulsivity in amateur soccer referees - López-Aguilar, Jose; Burgueno, Rafael; Castillo-Rodríguez, Alfonso; Onetti, Wanesa (PEERJ, 2022)
Soccer referees (SRs) are exposed to stressful situations during the competition that can affect decision-making, could be affected by impulsivity during the competition and therefore, require optimal psychological skills. The objective of this study was to ascertain and analyze the relationship between levels of impulsivity and self-efficacy of amateur SRs in the senior category. A total of 21 Spanish SRs participated in this study (age 23.57 +/- 2.40 years and 7.81 +/- 2.58 seasons of experience). Self-efficacy data were collected with the REFS questionnaire between 48 and 72 h before the competition. The impulsivity data were collected using the UPPS-P questionnaire 60 min before the start the competition. The results indicate that SRs with higher self-efficacy have lower levels of impulsivity, specifically in the dimensions of negative urgency (p < 0.01), positive urgency (p < 0.05), lack of premeditation (p < 0.001), and lack of perseverance (p < 0.001), as well as lower global impulsivity (p < 0.01). However, the SRs with the highest self-efficacy also obtained higher levels in the sensation seeking dimension (p < 0.05). In conclusion, the main finding of this study showed that self-efficacy is influenced by SR impulsivity prior to competition. These novel facts allow us to discover aspects related to decision-making in refereeing that can be trained to reach optimal levels.
Keywords: self-efficacy; impulsivity; personality; competition; football; referee; MANCOVA; UPPS Impulsive Behavior Scale; referee self-efficacy scale; JCR; Scopus